Is the Romanian organic grains value chain able to sustain the European Green Deal targets? - Iulia DAN; Valentin MIHAI; Ionel JITEA (Journal of Central European Agriculture)
Romania ranks among the top five cereal producers in the European Union, with an important organic grain sector. Currently, the existing research on organic value chains is relatively sparse. Furthermore, the geographical scope of the existing literature is often narrow, with limited attention to Eastern Europe, especially to Romania. Moreover, understanding the barriers of the organic value chain in line with the European Green Deal's ambition of certifying 25% of agricultural land as organic is also not properly addressed in the current literature. This study advances current knowledge by meticulously mapping the value chain structure in a multi-actor approach, aiming to identify governance issues and pinpoint barriers alongside potential solutions to maximise the contributions of the Romanian organic cereal sector to the EU Green Deal targets. Data was gathered through 30 semi-structured interviews with key stakeholders in the entire value chain. A content analysis was employed to interpret and categorise the findings at different stakeholder levels. Results reveal that several transversal challenges for better grains organic sector development are: inconsistent legislative frameworks; low processing capabilities attributed to the low demand for organic products, and the lack of consumer confidence in organic products. Stakeholders propose several strategies to mitigate these challenges, including the implementation of consumer education initiatives, a focus on boosting domestic processing instead of relying on exports, legislative stability and the introduction of better-targeted financial incentives to support organic farming. All these results collectively hinder the likelihood of achieving the organic farming targets outlined by the EU Green Deal.